Expanding industrial uses of sweetpotato for food security and poverty alleviation - Adu-Kwarteng, E.; Baafi, E.; Amoa-Owusu, A.; Okyere, F.; Carey, E.E. (Walter de Gruyter GmbH, 2021)
Sweetpotato breeding over the years solely depended on sensory evaluation for domestic uses, thereby downplaying the need for adjustment of breeding objectives and selection procedures to cater for industrial potential. This study was conducted to evaluate ten elite genotypes of sweetpotato for diversified utilization and commercialization. These genotypes had been selected over the years for high dry matter and starch content according to the preference of Ghanaian consumers. Analyses were carried out on key nutrient components, pasting properties, and starch granule morphology using near infrared reflectance spectroscopy, rapid viscosity analysis, and light microscopy, respectively. Sensory evaluation was carried out using a focus group approach. Based on functional diversity and unique combinations of quality traits identified, the genotypes were found to have several potential applications in the food industry. These include fufu flour, bread, pastries, French fries, gluten-free noodles, yogurt filler, baby food, juices, and raw material for brewery and other industries. These elite genotypes, when released as new varieties, can immensely contribute to a more diversified use of sweetpotato in Ghana and ultimately contribute to the enhancement of food and job security.